Dakwah Digital: Publikasi Kegiatan Masjid Memanfaatkan Jejaring Sosial - Alhasbi, Faruq; Faraba, Karina Sofiananda Armaza; Effendi, Arif; Utomo, Bagas Imam; Bachtiar, Farchan; Azizah, Ummi Nur (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
With its various features, social media facilitates organizations, including mosques, in interacting with the community. However, due to insufficient information dissemination, many residents around Al-Hikmah Mosque, Margoasri Karangmalang Sragen, remain unaware of its activities. Despite the mosque administrators being active, lacking information has resulted in low community participation, rendering the activities less than optimal. The digital da'wah training aims to provide an understanding of creating da'wah content via social networks, expanding the reach of religious institutions, and facilitating the publication and documentation of activities at Al-Hikmah Mosque. This community service program was conducted through a seminar followed by mentoring sessions. It fully employed the design thinking method to address the partners' issues by optimizing existing resources. Over four months, the service team engaged with the partners to understand their problems, conduct field observations, narrow down the issues, formulate solutions, and develop and implement the proposed ideas presented during the training. The training on publishing mosque activities using social networks brought significant changes to the community service partner. The partner successfully created an Instagram account to disseminate mosque-related information, expand the reach of da'wah, and document mosque activities. However, further training is needed to ensure consistency and enhance technical skills in managing social networks to support the mosque's da'wah efforts. Keywords: Digital da'wah, Da'wah content, Social networks, Mosque activities Abstrak: Media sosial dengan berbagai fiturnya mempermudah organisasi, termasuk masjid, berinteraksi dengan masyarakat. Namun, banyak warga sekitar Masjid Al-Hikmah Margoasri Karangmalang Sragen tidak mengetahui kegiatan masjid akibat kurangnya penyebaran informasi. Meski pengurus masjid aktif, keterbatasan informasi menyebabkan partisipasi masyarakat rendah, sehingga kegiatan belum optimal. Pelatihan dakwah digital bertujuan untuk memberikan pemahaman tentang pembuatan konten dakwah melalui jejaring sosial, perluasan jangkauan dakwah institusi keagamaan, serta memfasilitasi media publikasi informasi dan dokumentasi kegiatan di Masjid Al-Hikmah. Pengabdian ini dilaksa-nakan melalui seminar kemudian pendampingan, di mana secara utuh memakai metode design thinking untuk memecahkan masalah mitra melalui optimalisasi sumber daya yang ada. Selama empat bulan, Tim Pengabdian berkomunikasi dengan mitra untuk memahami permasalahan, observasi lapangan, mengerucutkan masalah, menyusun ide solusi masalah, pengembangan, dan penerapan ide-ide yang dipaparkan dalam materi pelatihan. Pelatihan publikasi kegiatan masjid dengan memanfaatkan jejaring sosial memberikan perubahan mitra PkM. Mitra akhirnya mempunyai akun Instagram untuk mempublikasikan informasi masjid, memperluas jangkauan dakwah, dan media dokumentasi aktivitas masjid. Meskipun begitu, masih diperlukan pelatihan lanjut terkait konsistensi dan kemampuan teknis dalam pengelolaan jejaring sosial yang bertendensi pada upaya dakwah masjid. Kata kunci: Dakwah digital, Kdakwah, Jejaring sosial, Kegiatan masjid